2014
DOI: 10.1158/1078-0432.ccr-13-3140
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Codon 12 and 13 Mutations in Relation to Disease-Free Survival in BRAF–Wild-Type Stage III Colon Cancers from an Adjuvant Chemotherapy Trial (N0147 Alliance)

Abstract: Purpose We examined the prognostic impact of specific KRAS mutations in stage III colon adenocarcinoma patients receiving adjuvant FOLFOX alone or combined with cetuximab in a phase III trial (N0147). Analysis was restricted to BRAF-wild type tumors, since BRAF mutation was associated with poor prognosis, and BRAF and KRAS mutations are mutually exclusive. Experimental Design The seven most common KRAS mutations in codon 12 and codon 13 were examined in 2,478 BRAF-wild type tumors. Because KRAS mutations in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
98
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 48 publications
(64 reference statements)
13
98
3
2
Order By: Relevance
“…The most common mutant alleles for KRAS are 12D, 12C, 12V, 12R, and 13D [144,145]. Evidence has shown that different KRAS mutant alleles may have different clinical impacts on the prognosis of lung [146,147], colon [148][149][150], and pancreatic [151] cancers, although the alleles associated with poor clinical outcomes are not consistent in these studies. Molecular characterization of clinical specimens from patients who participated in prospective phase II biomarker-integrated approaches of targeted therapy for lung cancer elimination revealed that the expressions of cell cycle regulators PLK1, CCNB1, and CCNE1 were lower in KRAS 12C and KRAS 12V mutant tumors, but were higher in the remaining KRAS mutant tumors, when compared with KRAS wild-type cancer [146].…”
Section: Studies On Clinical Specimens and Clinical Trialsmentioning
confidence: 85%
“…The most common mutant alleles for KRAS are 12D, 12C, 12V, 12R, and 13D [144,145]. Evidence has shown that different KRAS mutant alleles may have different clinical impacts on the prognosis of lung [146,147], colon [148][149][150], and pancreatic [151] cancers, although the alleles associated with poor clinical outcomes are not consistent in these studies. Molecular characterization of clinical specimens from patients who participated in prospective phase II biomarker-integrated approaches of targeted therapy for lung cancer elimination revealed that the expressions of cell cycle regulators PLK1, CCNB1, and CCNE1 were lower in KRAS 12C and KRAS 12V mutant tumors, but were higher in the remaining KRAS mutant tumors, when compared with KRAS wild-type cancer [146].…”
Section: Studies On Clinical Specimens and Clinical Trialsmentioning
confidence: 85%
“…In the Alliance N0147 trial, patients with KRAS exon 2 mutations experienced a shorter disease-free survival than patients without such mutations. 148 At this time, however, the test is not recommended for prognostic reasons.…”
Section: The Role Of Kras Nras and Braf Statusmentioning
confidence: 99%
“…Furthermore, Yoon et al [10] found that RCC was significantly associated with a shorter DFS compared with LCC when patients with BRAF-wild-type stage Ⅲ…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%